The accumulation of silver and gold in Lemna gibba L. exposed to secondary effluents - Şaşmaz, Ahmet; Öbek, Erdal (My University, 2012)
Aquatic plants are used as a practical and effective method to remove toxic metals from secondary-treated municipal wastewater. In this study, Lemna gibba was investigated for its capacity to remove silver (Ag) and gold (Au) from secondary effluents. L. gibba was collected from a natural lake and then acclimatized to the effluent in situ. The concentration of toxic elements in the plant material was monitored as a function of time over 7 days. L. gibba accumulated significant amounts of Ag and Au for six days from initiation of the experimental study. The highest accumulations were 2303% for Ag and 247% for Au. However, after six days, the rate of Ag and Au accumulation in L. gibba declined, as saturation levels had been reached in the plant tissues. The metal accumulating property of L. gibba can also be commercially exploited to recover Au and Ag from wastewater and mining wastes.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Bioaccumulation; Lemna gibba; Gold; Silver; Municipal wastewater